Role of c‐Jun N‐terminal kinase isoforms in the cellular activity of melanoma cell lines. (December 2013) - Kogushi‐Nishi, H.; Jinnin, M.; Kobayashi, Y.; Muchemwa, F. C.; Hirano, A.; Makino, T.; Fukushima, S.; Masuguchi, S.; Ishihara, T.; Inoue, Y.; Ihn, H.
Summary Background The c‐Jun N‐terminal kinase (JNK) is thought to be involved in inflammation, proliferation and apoptosis. Aim To examine the role of JNK isoforms in metastasis, proliferation, migration and invasion of the malignant melanoma (MM) cell lines SK‐MEL‐28, SK‐MEL‐3 and WM164, using a kinase‐specific inhibitor or isoform‐specific small interfering (si)RNAs. Results SK‐MEL‐3, a cell line established from metastatic MM, showed slightly increased phosphorylation of both JNK1 and JNK2, whereas WM164, a cell line derived from primary MM, showed significant phosphorylation of JNK1. A JNK inhibitor, SP600125, inhibited cell proliferation of SK‐MEL‐3 but not SK‐MEL‐28 or WM164. Transfection of JNK1‐specific siRNA reduced the migratory activity of WM164 cells, while silencing of either JNK1 or JNK2 strongly suppressed the invasive activity of SK‐MEL‐3. Conclusions Our study suggests that JNK isoforms have different roles in MM. Metastasis of MM may be regulated by JNK2, while invasion is regulated by both JNK1 and JNK2. JNK1 and JNK2 respectively mediate cell migration and cell proliferation. Further understanding of the specific roles of JNK isoforms in the pathogenesis of MM may lead to the development of therapies targeting specific isoforms.